Multiple daily injection of insulin regimen for a 10-month-old infant with type 1 diabetes mellitus and diabetic ketoacidosis - Ji Hyun Park; So Young Shin; Ye Jee Shim; Jin Hyeok Choi; Heung Sik Kim (Korean Society of Pediatric Endocrinology, 2016)
The incidence of type 1 diabetes is increasing worldwide, and the greatest increase has been observed in very young children under 4 years of age. A case of infantile diabetic ketoacidosis in a 10-month-old male infant was encountered by these authors. The infant's fasting glucose level was 490 mg/dL, his PH was 7.13, his pCO2 was 15 mmHg, and his bicarbonate level was 5.0 mmol/L. The glycosylated hemoglobin level had increased to 9.4%. Ketonuria and glucosuria were detected in the urinalysis. The fasting C-peptide and insulin levels had decreased. The infant was positive for anti-insulin and antiglutamic acid decarboxylase antibodies. Immediately after the infant's admission, fluid therapy and intravenous insulin infusion therapy were started. On the second day of the infant's hospitalization and after fluid therapy, he recovered from his lethargic condition, and his general condition improved. Feeding was started on the third day, and he was fed a formula 5 to 7 times a day and ate rice, vegetables, and lean meat. Due to the frequent feeding, the frequency of rapid-acting insulin injection was increased from 3 times before feeding to 5 times, adjusted according to the feeding frequency. The total dose of insulin that was injected was 0.8-1.1 IU/kg/day, and the infant was discharged on the 12th day of his hospitalization. The case is presented herein with a brief review of the relevant literature.